(3ejRGf GdebGOjQs - (3GdYGedj, GdYGedj, MSf Hf SdjeGf GdYGedj, Js ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj HjOg ebGOjQ GdCehQ (B... (3deG QGjJ Gdgee Yf eYQaI GdChRGf bGUQI (B... (3CQOJ Cf CWdb YfGf Gdbde aj ejOGf HjGfgG (B... (3hQJH Ydi Pdc ebOeI heWdHjf hNGJeI, CeG GdebOeI aajgG CHMGKs
(3BNQgG (B:s
(3BNQgG(B: (3aGYde Cf hRf GdQSJj jchf HGdOQGge SHYjf GdaG heGFJj OQge, hHGdeKGbjd GdTQYjI JSYI hCQHYjf CdaG hCQHYjf eKbGdG hHGdUjQajI SJI hKdGKjf CdaG hKeGf eFI eKbGdG hNeSI hNeSjf eKbGdG (B. (3NGJeIs
(3Je PcQ GdfGSN hJGQjN GdfSN GYJeGOG Ydi GdPQjYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B23: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis